Red Yeast Improves the Potential Safe Utilization of Solid Waste (Phosphogypsum and Titanogypsum) Through Bioleaching - Chen, Haoming; Lu, Yuqi; Zhang, Chaonan; Min, Fangfang; Huo, Zongli (Frontiers in Bioengineering and Biotechnology, 2021)
Phosphogypsum (PG) and titanium gypsum (TG), as a by-product (solid waste) in phosphate fertilizer and titanium dioxide industry, are causing serious environmental hazards. The biological function of red yeast (Rho: Rhodotorula mucilaginosa) can effectively reduce the inorganic or organic pollution in the environment. In order to achieve safe utilization of PG and TG, the bioremediation mechanism and safety utilization rate of different content of PG and TG by Rho were studied. The XRF results showed that F was the main toxic element in PG and TG, and Pb and Cd did not reach the detection limit. Rho has a high tolerance to PG (>10 g/mL), but low tolerance to TG (＜ 5 g/mL). After bioleaching by Rho, the proportion of F in PG and TG solid decreased by 61.45-63.79% and 49.45-59.19% respectively. The results of three-dimensional fluorescence, extracellular polymeric substances (EPS) extraction, XRD and SEM confirmed that Rho could accelerate the release of harmful elements (F) in PG and TG. In addition, the adsorption of EPS and the formation of Ca5(PO4)3F are two main ways for Rho to remove F. Furthermore, under the condition of high concentration bioleaching, Rho can accelerate the release and utilization of P in PG, not only for the re-precipitation of Ca5(PO4)3F, but also for the protection of microbial reproduction. Meanwhile, the purification/safe reuse of PG by Rho is easier than that of TG. Therefore, the toxicity of PG and TG bioleaching by Rho can be greatly reduced, suggesting the huge potential of Rho in soil improvement and remediation.